Lung anatomy and histology of the extant coelacanth shed light on the loss of air-breathing during deep-water adaptation in actinistians. Issue 3 (8th March 2017) - Cupello, Camila; Meunier, François J.; Herbin, Marc; Clément, Gaël; Brito, Paulo M.
Abstract : Lungs are specialized organs originated from the posterior pharyngeal cavity and considered as plesiomorphic for osteichthyans, as they are found in extant basal actinopterygians (i.e. Polypterus ) and in all major groups of extant sarcopterygians. The presence of a vestigial lung in adult stages of the extant coelacanth Latimeria chalumnae is the result of allometric growth during ontogeny, in relation with long-time adaptation to deep water. Here, we present the first detailed histological and anatomical description of the lung of Latimeria chalumnae, providing new insights into its arrested differentiation in an air-breathing complex, mainly represented by the absence of pneumocytes and of compartmentalization in the latest ontogenetic stages.